2001
DOI: 10.1186/rr160
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine regulation of asthmatic airway inflammation: role of airway smooth muscle

Abstract: ASM = airway smooth muscle; BAL = bronchoalveolar lavage; COX = cyclooxygenase; ECM = extracellular matrix; FGF = fibroblast growth factor; GM-CSF = granulocyte/macrophage-colony stimulating factor; IFN = interferon; IGF = insulin-like growth factor; IL = interleukin; LIF = leukaemia inhibitory factor; 5-LO = 5-lipoxygenase; LT = leukotriene; MCP = monocyte chemotactic protein; MHC = major histocompatibility complex; NO = nitric oxide; PDGF = platelet-derived growth factor; PG = prostaglandin; RANTES = regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…This is in keeping with increased protein levels of the proinflammatory cytokines IL-1␤ and TNF-␣, both of which are the downstream targets of NF-B. It has been reported that chronic production of IL-1␤ can lead to pulmonary inflammation, emphysema, airway remodeling, and bronchial hyperreactivity, which are the main features of asthma and COPD (23,31,35). Therefore, maternal smoking during pregnancy may increase the risk of chronic inflammatory conditions in offspring lungs, making them more susceptible to certain pulmonary disorders such as COPD in adulthood, which requires further investigation.…”
Section: L419mentioning
confidence: 76%
“…This is in keeping with increased protein levels of the proinflammatory cytokines IL-1␤ and TNF-␣, both of which are the downstream targets of NF-B. It has been reported that chronic production of IL-1␤ can lead to pulmonary inflammation, emphysema, airway remodeling, and bronchial hyperreactivity, which are the main features of asthma and COPD (23,31,35). Therefore, maternal smoking during pregnancy may increase the risk of chronic inflammatory conditions in offspring lungs, making them more susceptible to certain pulmonary disorders such as COPD in adulthood, which requires further investigation.…”
Section: L419mentioning
confidence: 76%
“…Activation of the TSLP receptor on HASM cells led to enhanced secretion of IL-6, IL-8/CXCL8 and eotaxin/CCL11 [41]. These mediators are well known for the roles in promoting mucus hypersecretion (IL-6), recruiting inflammatory cells to the airways (IL-8 and CCL11) as well as promoting differentiation of lymphocytes (IL-6) [42]. …”
Section: Airway Smooth Muscle Cells In Asthma Pathogenesismentioning
confidence: 99%
“…These cells are potent producers of cytokines, chemokines and extracellular matrix proteins [34][35][36][37]. Moreover, passively sensitized airway smooth muscle cells [38], and asthmatic fibroblasts [39] produce more extracellular matrix when compared to cells obtained from healthy controls and thus, exhibit a profibrotic state.…”
Section: Airway Smooth Muscle: Airway Hyper-responsiveness and Remodementioning
confidence: 99%